THE RIGHT OF PRISONERS ACCORDING TO THE IJARAH 'ALA AL-'AMAL CONTRACT: A STUDY AT CLASS III LHOKNGA PRISON, INDONESIA - Dedi Setiawan; Usman; Majdey Zawawi (JURISTA: Jurnal Hukum dan Keadilan, 2024)
Every prisoner has the right to guarantee work safety, wages or premiums from the results of their work. However, at the Lhoknga Class III Penitentiary, the fulfilment of this right is not yet optimal because there are no regulations or laws that determine the nominal amount or percentage of wages that prisoners must receive. Currently, the amount of wages received by inmates is only determined based on the policy of the Head of the local Correctional Institution.  This article aims to explain the wage process applied by the Lhoknga Class III Penitentiary to prisoners, as well as to explain how the wages of prisoners in this institution are determined based on the ijarah 'ala al-'amal agreement. To obtain data, the author used qualitative research methods. The main data was collected through interviews with respondents and informants who were considered to have relevant information regarding the problem under study. Meanwhile, secondary data was obtained from reading sources such as books, journals, articles and other materials related to this research topic. From the research results, the fulfilment of the right to wages for work has not been optimal. Some prisoners' work activities do not yet receive decent wages, while in other activities, prisoners earn wages of 33% from sales of goods or products.